Inovasi Sosial, Rantai Nilai, dan Dampak Ekonomi Program Menara Marina pada Pemanfaatan Limbah Aluminium dan Polyurethane Foam PT Badak NGL: Social Innovation, Value Chain, and Economic Environmental Impact of the Menara Marina Program on the Utilization of Aluminum and Polyurethane Foam Waste at PT Badak NGL - Kahar, Abdul; Busyairi, Muhammad; Jannah, Aulia Miftahul; Sihombing, Marista; Gunawan, Yuli; Putri, Dwi Thia; Sewakotama, Restra; Urfan, M. Yahdi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
PT Badak NGL's operations generate non-hazardous waste in the form of aluminum and polyurethane foam (PUF), which accumulates over time. Furthermore, the coastal and island people near Bontang experience low income, diminishing fish harvests, declining seaweed productivity, and high rates of unemployment and poverty. This rubbish is used commercially, socially, and environmentally in the Menara Marina Programme. The Menara Marina Program began with program initiation, capacity building, production trials, non-hazardous waste management and usage, product innovation creation, capital growth, and improved financial management. It focuses on social innovation, value chain development, and economic impact assessments for community organizations. Social innovation successfully encouraged community groups to add value by shifting the value chain between groups through mutually beneficial distribution and manufacturing higher-quality, longer-lasting products. The Telihan Recycle group produces boat propellers from aluminum insulation waste materials, which are then sold throughout Bontang and East Kalimantan. The Tanjung Mamat Fiberglass group utilizes PUF to make fishing boats, which have a durability ratio 1:10.625 compared to wood boats. The Marina Tihi-Tihi group uses PUF to produce floats to replace wasted mineral water bottles, with PUF floats lasting 15 years compared to 3 months.